Au / NiO / CeO2 difunctional photoelectric catalytic material as well as preparation method and application thereof
The Au/NiO/CeO2 material addresses the low catalytic performance of CeO2 composites by enhancing electron transfer and surface area, achieving efficient photocatalytic and electrocatalytic processes with a wide light response.
Patent Information
- Application Number
- CN202410929318.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-11
- Publication Date
- 2024-12-24
AI Technical Summary
Existing CeO2 composite materials exhibit low catalytic performance due to limited catalytic efficiency and narrow absorption range of visible light, which hinders their application in photocatalytic and electrocatalytic processes.
A dual-functional Au/NiO/CeO2 material is developed with a core-shell structure, featuring nickel oxide nanosheets on cerium dioxide hollow tubes and in-situ deposited gold nanoparticles, forming both a pn junction and an ohmic junction to enhance electron transfer and increase the specific surface area.
The Au/NiO/CeO2 material significantly improves photocatalytic degradation of organic pollutants and electrocatalytic OER performance with a wide light response range, demonstrating high efficiency and stability.
Smart Images

Figure HDA0004939166920000011 
Figure HDA0004939166920000012 
Figure HDA0004939166920000021
Abstract
Description
Technical Field
[0001] The invention relates to an Au / NiO / CeO2 dual-functional photoelectric catalytic material and a preparation method and application thereof, belonging to the technical field of inorganic photoelectric catalytic materials. Background Art
[0002] The rapid development of society has led to serious environmental pollution and energy crisis, which has prompted people to study the cleanliness and conversion of renewable energy. Water is a sustainable and abundant alternative energy source that plays an important role in solving environmental and energy problems. In solving environmental pollution, the removal of organic pollutants in wastewater is particularly important for the control and remediation of water pollution. Photocatalysis, as an efficient, economical and environmentally friendly green technology, offers great potential for the degradation of organic pollutants. On the other hand, electrocatalytic water decomposition is an important way to solve energy problems. Water splitting reactions include hydrogen evolution reaction (HER) and oxygen evolution reaction (OER). OER is a kinetically slow process (multiple electronic steps), which limits the efficiency of water decomposition. Therefore, it is crucial to develop efficient, stable catalysts with both photocatalytic and OER performance.
[0003] CeO2 is one of the most abundant rare earth oxides and an n-type semiconductor material with superior performance. It has attracted much attention due to its physical and chemical stability, environmental friendliness, non-toxicity, simple preparation method, and excellent electrical and optical properties. At the same time, CeO2 is a non-stoichiometric oxide. Since the valence state of Ce changes at any time, it can generate reversible redox pairs of Ce under unique environmental conditions. 3+ / Ce 4+ , showing great potential in promoting electron transfer, so CeO2 is an excellent catalyst.
[0004] NiO is an attractive p-type semiconductor material that has been widely used in catalysis due to its low cost, abundant content, and high electron-hole mobility. In addition, the rich edge structure and edge position effect of the two-dimensional structure make it easier to generate defects, thereby optimizing the band structure of nickel oxide. At the same time, NiO has Ni 2+ / Ni 3+ It can promote redox reactions. Due to the matching band structures of NiO and CeO2, the internal electric field formed by the NiO / CeO2p-n heterostructure can accelerate the separation efficiency of photogenerated carriers, thereby improving the catalytic efficiency. However, both NiO and CeO2 are semiconductors with large band gaps and low utilization of visible light. Therefore, the absorption range of the NiO / CeO2 pn heterostructure formed by NiO and CeO2 is narrow, which limits its application.
[0005] As a noble metal, Au has a surface plasmon resonance (SPR) effect, which can absorb incident visible light photons and convert them into more high-energy electrons.
[0006] Patent document CN104841443A discloses a method for preparing nanorod cerium dioxide-nickel oxide composite oxide. The method uses soluble cerium salt and nickel salt as cerium source and nickel source respectively, adds excessive precipitant, reacts under alkaline conditions to generate precipitate, and then hydrothermally reacts at 80-180°C. The hydrothermal reaction product is dried and calcined at 300-500°C to obtain nanorod cerium dioxide-nickel oxide composite oxide. It can be seen from the recorded drawings that the microscopic morphology of the material is nanorod, resulting in a small surface area and few reactive sites, which greatly limits the catalytic efficiency.
[0007] Most of the CeO2 composite materials reported so far are pn junction materials, and their catalytic performance still needs to be improved. Summary of the invention
[0008] In view of the shortcomings of the prior art, especially the problem that the catalytic performance of the existing CeO2 composite materials is still relatively low, the present invention provides an Au / NiO / CeO2 dual-functional photoelectrocatalytic material and a preparation method and application thereof.
[0009] The Au / NiO / CeO2 bifunctional photoelectrocatalytic material of the present invention has both a pn junction and an ohmic junction. The interaction between gold, cerium dioxide and nickel oxide can effectively promote electron transfer, enhance the interaction between interfaces, greatly improve the photoelectrocatalytic efficiency, and has a large specific surface area, which significantly improves the photocatalytic degradation of rhodamine B and electrocatalytic OER performance, while also having a wide light response range.
[0010] The present invention is achieved through the following technical solutions:
[0011] The invention discloses an Au / NiO / CeO2 dual-function photoelectrocatalytic material, whose microscopic morphology is that nickel oxide nanosheets are loaded on the surface of a cerium dioxide hollow tube, Au nanoparticles are in-situ deposited on the surface of the nanosheets, and the material has a pn junction and an ohmic junction.
[0012] According to the present invention, the method for preparing the Au / NiO / CeO2 bifunctional photoelectrocatalytic material comprises the following steps:
[0013] (1) adding nickel acetate, hexamethylenetetramine and sodium citrate into water and mixing them evenly, then adding a cerium dioxide hollow tube and stirring with a magnetic stirrer to obtain a mixed solution a;
[0014] (2) The mixed solution a is heated in an oil bath, and the obtained precipitate is cross-washed with deionized water and ethanol, and dried to obtain a precursor of nickel oxide and cerium dioxide.
[0015] (3) calcining a nickel oxide / cerium dioxide precursor to obtain a nickel oxide / cerium dioxide composite material;
[0016] (4) Adding chloroauric acid trihydrate (HAuCl4·3H2O) solution to the nickel oxide / cerium dioxide composite material, dispersing it in a mixed solution b of deionized water and methanol, and performing photodeposition to obtain Au / NiO / CeO2 bifunctional photoelectrocatalytic material.
[0017] Preferably according to the present invention, in step (1), the mass ratio of nickel acetate to hexamethylenetetramine is 1:(0.3-0.9).
[0018] Preferably according to the present invention, in step (1), the mass ratio of nickel acetate to sodium citrate is 1:(0.1-0.5).
[0019] Preferably, according to the present invention, in step (1), the mass ratio of nickel acetate to cerium dioxide hollow tube is 1:(0.1-0.5).
[0020] Preferably according to the present invention, in step (1), the mass volume ratio of nickel acetate to water is (0.1-0.5) g: (50-70) mL.
[0021] According to the preferred embodiment of the present invention, in step (1), the cerium dioxide hollow tube is prepared by the following method:
[0022] 1) mixing ethanol and N,N-dimethylformamide solution, adding cerium trichloride, and then adding PVP, and stirring magnetically to mix the solution evenly to obtain a spinnable precursor sol;
[0023] 2) electrospinning the spinnable precursor sol obtained in step 1) to obtain precursor fibers;
[0024] 3) Dry the precursor fiber obtained in step 2) at 40-100° C. for 12-36 hours, heat it to 200-600° C. at a rate of 1-5° C. / min, and calcine it for 60-180 minutes to obtain a cerium dioxide hollow tube.
[0025] Preferably according to the present invention, in step 1), the volume ratio of ethanol to N,N-dimethylformamide solution is (0.5-2):1.
[0026] Most preferably, in step 1), the volume ratio of ethanol to N,N-dimethylformamide solution is 1:1.
[0027] According to the preferred embodiment of the present invention, in step 1), the weight average molecular weight of the polyvinyl pyrrolidone is 40,000-3,000,000; most preferably, the weight average molecular weight of the polyvinyl pyrrolidone is 1,300,000. The best nanofiber photocatalytic material can be obtained.
[0028] Preferably according to the present invention, in step 1), the mass ratio of PVP to cerium trichloride is 1:(1-1.5).
[0029] Preferably according to the present invention, in step 1), the magnetic stirring time is 8-20 hours.
[0030] Preferably, according to the present invention, in step 2), the spinnable precursor sol obtained in step 1) is subjected to electrospinning at a temperature of 15-35° C., a voltage of 10-30 kV, and a spraying rate of 0.1-1.5 mL / h.
[0031] Preferably according to the present invention, in step 3), the drying temperature of the precursor fiber is 40-60° C., and the drying time is 12-24 hours.
[0032] Preferably according to the present invention, in step 3), the calcination temperature is 400-600° C., the calcination time is 120 min, and the heating rate is 2° C. / min.
[0033] Preferably according to the present invention, in step (2), the oil bath heating temperature is 80-100° C., and the oil bath heating time is 4-10 h.
[0034] Most preferably, in step (2), the oil bath heating temperature is 90° C. and the oil bath heating time is 8 h.
[0035] Preferably according to the present invention, in step (2), the drying is carried out in an oven at a drying temperature of 40-100° C. and a drying time of 8-24 h.
[0036] Preferably according to the present invention, in step (3), the calcination temperature is 200-400° C. and the drying time is 1-4 h.
[0037] Most preferably, in step (3), the calcination temperature is 300° C. and the drying time is 2 h.
[0038] Preferably according to the present invention, in step (4), the concentration of the chloroauric acid trihydrate solution is 2-6 mol / L.
[0039] Preferably, according to the present invention, in step (4), the mass volume ratio of the amount of the nickel oxide / cerium dioxide composite material to the chloroauric acid trihydrate solution is 1:(2-8), unit, mg / μL.
[0040] Preferably according to the present invention, in step (4), the volume ratio of methanol to deionized water in the mixed solution b is 1:(6-12).
[0041] Preferably, according to the present invention, in step (4), the mass volume ratio of the amount of the nickel oxide / cerium dioxide composite material to the mixed solution b is 1:(1-6), unit, mg / μL.
[0042] Preferably, in step (4), the photodeposition is: irradiating the NiO / CeO2 surface with a 300W xenon lamp to simulate sunlight for 1-8 hours, and Au photodeposition occurs at room temperature on the NiO / CeO2 surface.
[0043] The Au content in the Au / NiO / CeO2 bifunctional photoelectrocatalytic material is 4-8wt%, and most preferably, the Au content in the Au / NiO / CeO2 bifunctional photoelectrocatalytic material is 5wt%.
[0044] The application of the above-mentioned Au / NiO / CeO2 bifunctional photoelectrocatalytic material, the Au / NiO / CeO2 bifunctional photoelectrocatalytic material has the dual functions of photocatalytic degradation of pollutants and electrocatalytic OER, and is used for photocatalytic degradation of organic pollutants under sunlight or for electrocatalytic OER.
[0045] Preferably according to the present invention, when used for photocatalytic degradation of organic pollutants under sunlight, the organic pollutant is rhodamine B (RhB), and the concentration of the organic pollutant is 5-20 mg / L; the amount of Au / NiO / CeO2 photocatalytic material and the volume of the organic pollutant are (1-4):(4-6), unit, mg / mL.
[0046] Preferably according to the present invention, when used for electrocatalytic OER, the electrolyte is a 0.5-3M KOH solution, and the scanning speed is 10 mV / s.
[0047] Features and beneficial effects of the present invention:
[0048] 1. The Au / NiO / CeO2 bifunctional photoelectrocatalytic material of the present invention has both a pn junction and an ohmic junction, and has the dual functions of photocatalytic degradation of pollutants and electrocatalytic OER. The interaction between gold, cerium dioxide and nickel oxide can effectively promote electron transfer, enhance the interaction between interfaces, greatly improve the photoelectrocatalytic efficiency, and has a large specific surface area, which significantly improves the photocatalytic degradation and electrocatalytic OER performances, and also has a wide light response range.
[0049] 2. The Au / NiO / CeO2 bifunctional photoelectric catalytic material of the present invention, the Schottky junction formed by Au / NiO and the pn junction formed by NiO / CeO2 can effectively separate photogenerated electron-hole pairs, thereby greatly improving the photocatalytic performance.
[0050] 3. The Au / NiO / CeO2 dual-function photoelectrocatalytic material of the present invention has Ni 2+ / Ni 2+ 、Ce 3+ / Ce 4+ The conversion of redox pairs can promote the transfer of electrons and thus promote redox reactions.
[0051] 4. The Au / NiO / CeO2 dual-function photocatalytic material of the present invention is a core-shell structure, and its scanning electron microscopy shows Figure 2 g. Figure 2 h, NiO nanosheets and Au nanoparticles loaded on the surface of CeO2 hollow tubes not only have a larger specific surface area, but also increase the path of electron transfer, thereby improving the photocatalytic performance of the resulting composite material.
[0052] 5. The Au / NiO / CeO2 dual-functional photoelectric catalytic material of the present invention can be recycled, which greatly reduces the production cost.
[0053] 6. The preparation method of the present invention is simple, the process equipment is simple, and it is easy to operate. BRIEF DESCRIPTION OF THE DRAWINGS
[0054] Figure 1 is the XRD spectra of the photoelectrocatalytic material samples prepared in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3;
[0055] Figure 2 The scanning electron microscope (SEM) and transmission electron microscope (TEM) photos of the photoelectrocatalytic materials prepared in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 are shown in Figures a and b are for Comparative Example 1, c and d are for Comparative Example 2, e and f are for Comparative Example 3, and g and h are for Example 1;
[0056] Figure 3 This is the absorbance curve of CeO2 photodegradation of Rhodamine B prepared in Comparative Example 1; the curves in the figure correspond to 0-90min from top to bottom in the figure;
[0057] Figure 4 This is the absorbance curve of NiO photodegradation of Rhodamine B prepared in Comparative Example 2; the curves in the figure correspond to 0-90min from top to bottom in the figure;
[0058] Figure 5 The absorbance curve of NiO / CeO2 photodegradation of Rhodamine B prepared in Comparative Example 3; the curves in the figure correspond to 0-90 min from top to bottom in the figure.
[0059] Figure 6 This is the absorbance curve of the photodegradation of Rhodamine B by the Au / NiO / CeO2 heterostructure prepared in Example 1 of the present invention; the curves in the figure correspond to 0-90min from top to bottom in sequence;
[0060] Figure 7 is a comparison chart of the degradation of Rhodamine B by the photocatalytic materials prepared in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3;
[0061] Figure 8This is a graph showing the degradation efficiency of Rhodamine B after four cycles of degradation of the photocatalytic material prepared in Example 1.
[0062] Fig. 9 1 is the LSV curve of the electrocatalytic materials prepared in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3.
[0063] Fig.10 1 is the double-layer capacitance curve of the electrocatalytic materials prepared in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3.
[0064] Fig.11 This is a stability test performance diagram of the electrocatalytic material prepared in Example 1. DETAILED DESCRIPTION
[0065] The present invention will be further described below in conjunction with specific embodiments, and the advantages and features of the present invention will become clearer as the description proceeds. However, the embodiments are exemplary only and do not constitute any limitation to the scope of the present invention. It should be understood by those skilled in the art that the details and forms of the technical solution of the present invention may be modified or replaced without departing from the spirit and scope of the present invention, but these modifications and replacements all fall within the scope of protection of the present invention. The raw materials used are all conventional reagents, commercially available products.
[0066] Example 1
[0067] The preparation method of Au / NiO / CeO2 dual-functional photoelectrocatalytic material, the steps are as follows:
[0068] (1) 2.5 mL of ethanol and 2.5 mL of N,N-dimethylformamide solution were mixed, 0.25 g of cerium trichloride was added, and then 0.34 g of PVP was added, and magnetic stirring was performed for 12 h to mix the solution evenly to obtain a spinnable precursor sol;
[0069] (2) electrospinning the spinnable precursor sol obtained in step (1) at a temperature of 25° C., a voltage of 15 kV, and a spraying rate of 1 mL / h to obtain a precursor fiber;
[0070] (3) drying the precursor fiber obtained in step (2) at 40° C. for 12 h, heating to 500° C. at a rate of 2° C. / min, and keeping the temperature for 120 min to obtain a cerium dioxide hollow tube;
[0071] (4) 0.124 g of nickel acetate, 0.07 g of hexamethylenetetramine and 0.0147 g of sodium citrate were added to a beaker containing 60 mL of deionized water, and 40 mg of the cerium dioxide hollow tube obtained in step (3) was added, and magnetic stirring was performed to obtain a mixed solution a;
[0072] (5) heating the mixed solution a in an oil bath at 90°C for 8 h;
[0073] (6) The precipitate obtained in step (5) is cross-cleaned with deionized water and ethanol, and dried in an oven at 60° C. for 12 h to obtain a precursor of nickel oxide and cerium dioxide.
[0074] (7) The nickel oxide-cerium dioxide precursor is placed in a muffle furnace at a heating rate of 2°C / min and a calcination temperature of 300°C to obtain a nickel oxide-cerium dioxide photocatalytic material.
[0075] (8) 0.01 g of NiO / CeO2 prepared in step (7) was dispersed into a mixed solution formed by 4 mL of methanol and 36 mL of H2O, and then 50 μL of HAuCl4·3H2O (concentration of 5 mol / L) was added to the above solution. Au was photodeposited on the surface of NiO / CeO2 at room temperature under 300 W xenon lamp irradiation for 6 h to simulate sunlight;
[0076] The X-ray diffraction (XRD) spectrum of the Au / NiO / CeO2 heterostructure photocatalytic material prepared in this example is as follows: Figure 1 As shown by Figure 1 It can be seen that the diffraction peaks of the Au / NiO / CeO2 heterostructure correspond well to Au (JCPDS No.04-0784), CeO2 (JCPDS No.21-0102) and NiO (JCPDS No.47-1049), indicating that the Au / NiO / CeO2 heterostructure photocatalytic material was successfully prepared.
[0077] The SEM and TEM images of the Au / NiO / CeO2 heterostructure photocatalytic material prepared in this example are shown in FIG. Figure 2 As shown, through Figure 2 g, 2h, it can be seen that the microscopic morphology is that nickel oxide nanosheets are loaded on the surface of the ceria hollow tubes, and Au nanoparticles are loaded on the surface of the nickel oxide nanosheets.
[0078] Comparative Example 1
[0079] Preparation of CeO2 photocatalytic materials
[0080] (1) 2.5 mL of ethanol and 2.5 mL of N,N-dimethylformamide solution were mixed, 0.25 g of cerium trichloride was added, and then 0.34 g of PVP was added, and magnetic stirring was performed for 12 h to mix the solution evenly to obtain a spinnable precursor sol;
[0081] (2) electrospinning the spinnable precursor sol obtained in step (1) at a temperature of 25° C., a voltage of 15 kV, and a spraying rate of 1 mL / h to obtain a precursor fiber;
[0082] (3) The precursor fiber obtained in step (2) was dried at 40° C. for 12 h, heated to 500° C. at a rate of 2° C. / min, and kept warm for 120 min to obtain a cerium dioxide hollow tube photocatalytic material.
[0083] The X-ray diffraction (XRD) spectrum of the prepared CeO2 photocatalytic material is as follows: Figure 1 As shown by Figure 1 It can be seen that the diffraction peak of CeO2 corresponds to CeO2 (JCPDS No.21-0102). SEM and TEM images are shown in Figure 2 As shown, through Figure 2 The CeO2 shown in a and b is a hollow tube structure.
[0084] Comparative Example 2
[0085] Preparation of NiO photocatalytic materials
[0086] (1) 0.124 g of nickel acetate, 0.07 g of hexamethylenetetramine and 0.0147 g of sodium citrate were added to a beaker containing 60 mL of deionized water, and magnetic stirring was performed to obtain a mixed solution a;
[0087] (2) heating the mixed solution a in an oil bath at 90°C for 8 h;
[0088] (3) The precipitate obtained in step (2) is cross-cleaned with deionized water and ethanol, and dried in an oven at 60° C. for 12 h to obtain a nickel oxide precursor.
[0089] (4) The nickel oxide and cerium dioxide precursors are placed in a muffle furnace at a heating rate of 2°C / min and a calcination temperature of 300°C to obtain a nickel oxide photocatalytic material.
[0090] The X-ray diffraction (XRD) spectrum of the prepared NiO photocatalytic material is as follows: Figure 1 As shown by Figure 1 It can be seen that the diffraction peaks of NiO correspond well to those of NiO (JCPDS No.47-0149). Figure 2 As shown, through Figure 2 The NiO shown in c and d is a nanoflower structure.
[0091] Comparative Example 3
[0092] The preparation method of NiO / CeO2 photocatalytic material comprises the following steps:
[0093] (1) 2.5 mL of ethanol and 2.5 mL of N,N-dimethylformamide solution were mixed, 0.25 g of cerium trichloride was added, and then 0.34 g of PVP was added, and magnetic stirring was performed for 12 h to mix the solution evenly to obtain a spinnable precursor sol;
[0094] (2) electrospinning the spinnable precursor sol obtained in step (1) at a temperature of 25° C., a voltage of 15 kV, and a spraying rate of 1 mL / h to obtain a precursor fiber;
[0095] (3) drying the precursor fiber obtained in step (2) at 40° C. for 12 h, heating to 500° C. at a rate of 2° C. / min, and keeping the temperature for 120 min to obtain a cerium dioxide hollow tube photocatalytic material;
[0096] (4) 0.124 g of nickel acetate, 0.07 g of hexamethylenetetramine and 0.0147 g of sodium citrate were added to a beaker containing 60 mL of deionized water, and 40 mg of the cerium dioxide hollow tube obtained in step (3) was added, and magnetic stirring was performed to obtain a mixed solution a;
[0097] (5) heating the mixed solution a in an oil bath at 90°C for 8 h;
[0098] (6) The precipitate obtained in step (5) is cross-cleaned with deionized water and ethanol, and dried in an oven at 60° C. for 12 h to obtain a precursor of nickel oxide and cerium dioxide.
[0099] (7) The nickel oxide and ceria precursor are placed in a muffle furnace at a heating rate of 2°C / min and a calcination temperature of 300°C to obtain a nickel oxide and ceria photocatalytic material.
[0100] The X-ray diffraction (XRD) spectrum of the NiO / CeO2 heterostructure photocatalytic material prepared in this comparative example is as follows: Figure 1 As shown by Figure 1 It can be seen that the diffraction peaks of the NiO / CeO2 heterostructure correspond well to those of CeO2 (JCPDS No.21-0102) and NiO (JCPDS No.47-1049).
[0101] The SEM and TEM images of the NiO / CeO2 heterostructure photocatalytic material prepared in this comparative example are shown in FIG. Figure 2 As shown, through Figure 2 e and f, it can be observed that the microscopic morphology is that nickel oxide nanosheets are loaded on the surface of the ceria hollow tube.
[0102] From the comparison of the morphology of Example 1 of the present invention and Comparative Examples 1-3, it can be seen that the method of the present invention does not change the morphology of the cerium dioxide hollow tube.
[0103] Experimental Example 1
[0104] Photocatalytic oxidation degradation performance
[0105] The photocatalytic material samples prepared in Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3 were applied to the photocatalytic oxidation degradation experiment of Rhodamine B. The light source was a 350W xenon lamp, and the concentration of the Rhodamine B solution was 10 mg / L.
[0106] Here are the steps:
[0107] First, at room temperature, add 0.03g of photocatalytic material to 50mL of Rhodamine B solution, then place it in a dark box and stir it magnetically for 30min to reach adsorption-desorption equilibrium, and take out 4mL of solution after the dark reaction is completed; then, turn on the simulated light source and take out 4mL of solution every 15min; centrifuge the solution taken out each time to take the upper clear liquid, and use a UV-2550 spectrophotometer to test the absorbance of the supernatant at the highest peak (554nm); and recover the photocatalytic material. Formula (I):
[0108] η=[(C0-C t ) / C0]×100%,
[0109] In formula (I), C0 is the absorbance of the solution measured for the first time, C t is the absorbance measured at time t.
[0110] Figure 3 is the absorbance curve of the CeO2 hollow tube photodegradation of Rhodamine B prepared in Comparative Example 1 of the present invention, Figure 3 It can be seen that the degradation efficiency is 39.3% at 90 min;
[0111] Figure 4 is the absorbance curve of NiO prepared in Comparative Example 2 of the present invention in photodegradation of Rhodamine B; Figure 4 It can be seen that the degradation efficiency is 30.1% at 90 min;
[0112] Figure 5 is the absorbance curve of the NiO / CeO2 heterostructure prepared in Comparative Example 3 of the present invention in the photodegradation of Rhodamine B; Figure 5 It can be seen that the degradation efficiency is 84.8% in 90 min;
[0113] Figure 6 is the absorbance curve of Au / NiO / CeO2 heterostructure prepared in Example 1 of the present invention during photodegradation of Rhodamine B; Figure 5 It can be seen that the degradation efficiency is 93.9% in 90 min;
[0114] Figure 7The comparison diagram of the photocatalytic material for the degradation of Rhodamine B prepared by Comparative Example 1, Comparative Example 2, Comparative Example 3 and Example 1 is shown in FIG. Figure 7 It can be seen that the degradation rate of Example 1 at 90 min is the highest.
[0115] Experimental Example 2
[0116] Cycle performance
[0117] The photocatalytic material prepared in Example 1 was subjected to a cyclic performance test for photocatalytic degradation of Rhodamine B.
[0118] The degradation efficiency of Rhodamine B by the Au / NiO / CeO2 heterojunction photocatalytic material prepared in Example 1 after four cycles under simulated sunlight is shown in the figure. Figure 8 shown.
[0119] Depend on Figure 8 It can be seen that the Au / NiO / CeO2 heterostructure prepared in Example 1 still maintains a degradation rate of more than 90% in the experiment of four-cycle photodegradation of Rhodamine B, which proves that the sample has good stability.
[0120] Experimental Example 3
[0121] OER catalytic performance
[0122] The performance test method of OER is as follows: a three-electrode system is used, with the sample-coated glassy carbon electrode as the working electrode, the platinum wire as the counter electrode, and the Hg / HgO electrode as the reference electrode. The electrolyte used is 1M KOH solution. Oxygen is introduced before the test to saturate the electrolyte with oxygen. The scanning speed is 10mV / s.
[0123] Fig. 9 This is an OER polarization curve diagram of the electrocatalytic materials prepared in Example 1 and Comparative Examples 1, 2, and 3 in an O2-saturated 1M KOH solution at a scanning rate of 10 mV / s.
[0124] Depend on Fig. 9 It can be seen that the Au / NiO / CeO2 electrocatalytic material prepared in Example 1 has better OER catalytic performance than the electrocatalytic materials prepared in Comparative Examples 1, 2, and 3.
[0125] Experimental Example 4
[0126] Double layer capacitance test
[0127] The electrochemical double layer capacitance (C) of the Au / NiO / CeO2 electrocatalyst prepared in Example 1 was measured by cyclic voltammetry. dl ). Tested at 20, 40, 60, 80 and 100 mV s in the non-Faraday range. -1The CV curves at different scan rates are obtained. The half of the positive and negative current density difference (at the center of the potential range) is plotted against the scan rate, and the slope obtained by fitting is the double layer capacitance.
[0128] Depend on Fig.10 It can be seen that the Au / NiO / CeO2 electrocatalytic material prepared in Example 1 has a higher double-layer capacitance than the electrocatalytic materials prepared in Comparative Examples 1, 2, and 3, indicating that the Au / NiO / CeO2 electrocatalytic material has the highest electrochemical active area, thereby having more active sites.
[0129] Experimental Example 5
[0130] Stability performance test
[0131] The water electrolysis test is carried out in a two-electrode system. The two-electrode system is to connect the WE clamp to the working electrode as the anode, and the reference electrode clamp and the counter electrode clamp are connected together to the cathode.
[0132] Electrode preparation method: Mix the three chemicals in a mortar with the ratio of product of Example 1: acetylene black: PVDF = 8:1:1 and grind them evenly, then drip 3-4 drops of NMP and grind them thoroughly. Fold a 1*2 nickel sheet in half with tweezers, and evenly distribute the ground sample on the 1*1 area of the nickel sheet. Then place it in a vacuum drying oven at 60°C to dry, and use the dried nickel sheet after flattening it with a tablet press.
[0133] The test used 1M KOH solution as the electrolyte, fixed the prepared nickel sheet at one end of the electrode, and clamped the two electrodes for testing. First, the cyclic voltammetry test was performed with the activated electrode scanning rate of 0.05V s-1 and the voltage range of 1 to 2V, and then the linear sweep voltammetry was used to test the electrolysis performance of water.
[0134] Fig.11 The stability performance test of the Au / NiO / CeO2 electrocatalytic material prepared in Example 1 showed that after 24 hours of testing, the current density remained basically unchanged, indicating that the Au / NiO / CeO2 electrocatalytic material has excellent stability.
[0135] Example 2
[0136] The method for preparing the Au / NiO / CeO2 dual-functional photoelectrocatalytic material is the same as that described in Example 1, except that:
[0137] In step (4), the amount of nickel acetate was replaced with 0.233 g, and the rest was carried out as in Example 1.
[0138] Example 3
[0139] The method for preparing the Au / NiO / CeO2 dual-functional photoelectrocatalytic material is the same as that described in Example 1, except that:
[0140] In step (4), the amount of nickel acetate is replaced with 0.0875 g, and the rest is carried out as in Example 1.
[0141] Example 4
[0142] The method for preparing the Au / NiO / CeO2 dual-functional photoelectrocatalytic material is the same as that described in Example 1, except that:
[0143] In step (8), the amount of HAuCl4·3H2O solution was replaced with 30 μL, and the rest was carried out as in Example 1.
[0144] Example 5
[0145] The method for preparing the Au / NiO / CeO2 dual-functional photoelectrocatalytic material is the same as that described in Example 1, except that:
[0146] In step (8), the amount of HAuCl4·3H2O solution was replaced with 60 μL, and the rest was carried out as in Example 1.
Claims
1. An Au / NiO / CeO2 dual-functional photoelectrocatalytic material, whose microscopic morphology is nickel oxide nanosheets loaded on the surface of cerium dioxide hollow tubes, Au nanoparticles are in-situ deposited on the surface of the nanosheets, and has a pn junction and an ohmic junction.
2. The method for preparing the Au / NiO / CeO2 bifunctional photoelectrocatalytic material according to claim 1, comprising the following steps: (1) adding nickel acetate, hexamethylenetetramine and sodium citrate into water and mixing them evenly, then adding a cerium dioxide hollow tube and stirring with a magnetic stirrer to obtain a mixed solution a; (2) heating the mixed solution a in an oil bath, washing the obtained precipitate with deionized water and ethanol, and drying, thereby obtaining a precursor of nickel oxide and cerium dioxide; (3) calcining a nickel oxide / cerium dioxide precursor to obtain a nickel oxide / cerium dioxide composite material; (4) Adding chloroauric acid trihydrate (HAuCl4·3H2O) solution to the nickel oxide / cerium dioxide composite material, dispersing it in a mixed solution b of deionized water and methanol, and performing photodeposition to obtain Au / NiO / CeO2 bifunctional photoelectrocatalytic material.
3. The preparation method according to claim 2, characterized in that: In step (1), the mass ratio of nickel acetate to hexamethylenetetramine is 1:(0.3-0.9), the mass ratio of nickel acetate to sodium citrate is 1:(0.1-0.5), the mass ratio of nickel acetate to cerium dioxide hollow tube is 1:(0.1-0.5), and the mass volume ratio of nickel acetate to water is (0.1-0.5) g:(50-70) mL.
4. The preparation method according to claim 2, characterized in that: In step (1), the cerium dioxide hollow tube is prepared by the following method: 1) mixing ethanol and N,N-dimethylformamide solution, adding cerium trichloride, and then adding PVP, and stirring magnetically to mix the solution evenly to obtain a spinnable precursor sol; 2) electrospinning the spinnable precursor sol obtained in step 1) to obtain precursor fibers; 3) Dry the precursor fiber obtained in step 2) at 40-100° C. for 12-36 hours, heat it to 200-600° C. at a rate of 1-5° C. / min, and calcine it for 60-180 minutes to obtain a cerium dioxide hollow tube.
5. The preparation method according to claim 4, characterized in that: In step 1), the volume ratio of ethanol to N,N-dimethylformamide solution is (0.5-2):1, the weight average molecular weight of the polyvinyl pyrrolidone is 40,000-3,000,000, the mass ratio of PVP to cerium trichloride is 1:(1-1.5), and the magnetic stirring time is 8-20h. In step 2), the spinnable precursor sol obtained in step 1) is electrospun at a temperature of 15-35°C, a voltage of 10-30kV, and a spray rate of 0.1-1.5mL / h. In step 3), the drying temperature of the precursor fiber is 40-60°C, and the drying time is 12-24h. In step 3), the calcination temperature is 400-600°C, the calcination time is 120min, and the heating rate is 2°C / min.
6. The preparation method according to claim 1, characterized in that: In step (2), the oil bath heating temperature is 80-100° C., and the oil bath heating time is 4-10 hours. In step (2), the drying is carried out in an oven, the drying temperature is 40-100° C., and the drying time is 8-24 hours.
7. The preparation method according to claim 4, characterized in that: In step (3), the calcination temperature is 200-400° C. and the drying time is 1-4 hours.
8. The preparation method according to claim 4, characterized in that: In step (4), the concentration of the trihydrate chloroauric acid solution is 2-6 mol / L, the mass volume ratio of the amount of the nickel oxide / cerium dioxide composite material to the trihydrate chloroauric acid solution is 1:(2-8), unit, mg / μL, the volume ratio of methanol to deionized water in the mixed solution b is 1:(6-12), the mass volume ratio of the amount of the nickel oxide / cerium dioxide composite material to the mixed solution b is 1:(1-6), unit, mg / μL, and the photodeposition is: irradiated under a 300W xenon lamp to simulate sunlight for 1-8 hours, and Au photodeposition occurs on the NiO / CeO2 surface at room temperature.
9. Application of the Au / NiO / CeO2 bifunctional photoelectrocatalytic material according to claim 1, wherein the Au / NiO / CeO2 bifunctional photoelectrocatalytic material has the dual functions of photocatalytic degradation of pollutants and electrocatalytic OER, and is used for photocatalytic degradation of organic pollutants under sunlight or for electrocatalytic OER.
10. The use according to claim 9, characterized in that: When used for photocatalytic degradation of organic pollutants under sunlight, the organic pollutant is rhodamine B (RhB), and the concentration of the organic pollutant is 5-20 mg / L; the amount of Au / NiO / CeO2 photocatalytic material and the volume of the organic pollutant are (1-4):(4-6), unit, mg / mL, and when used for electrocatalytic OER, the electrolyte is 0.5-3M KOH solution, and the scanning speed is 10 mV / s.
Citation Information
Patent Citations
Preparation method for nanorod cerium dioxide-nickel oxide composite oxide
CN104841443A
